2020
DOI: 10.26434/chemrxiv.12651017
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Peritectic Phase Transition of Benzene and Acetonitrile and Formation of a Cocrystal Relevant to Titan, Saturn’s Icy Moon

Abstract: Benzene and acetonitrile are two of the most commonly used solvents found in almost every chemical laboratory. Titan, Saturn’s icy moon, is one other place in the Solar system that has even larger amounts of these compounds, together with many other hydrocarbons. On Titan, organic molecules are produced in the atmosphere and carried by methane rainfall to the surface, where they either dissolve in the lakes, deposit as sandy dunes, or solidify as minerals with complex composition and structure. In order to unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Experimental methods include neutron and x-ray diffraction. It can be observed that the data from the work of Dunitz and Ibberson (above 200 K), 65 Fortes and Capelli (above 200 K), 66 Heydweiller, 79 and McConville et al 82 deviate by up to 0.5% from the model at a given temperature and contribute to most of the deviations in the plot. These data sources were kept in the regression process, as only outliers that deviate from the other data points by more than 1% were excluded.…”
Section: Vmmentioning
confidence: 92%
“…Experimental methods include neutron and x-ray diffraction. It can be observed that the data from the work of Dunitz and Ibberson (above 200 K), 65 Fortes and Capelli (above 200 K), 66 Heydweiller, 79 and McConville et al 82 deviate by up to 0.5% from the model at a given temperature and contribute to most of the deviations in the plot. These data sources were kept in the regression process, as only outliers that deviate from the other data points by more than 1% were excluded.…”
Section: Vmmentioning
confidence: 92%